(untitled) (Italian Journal of Public Health, 2012)
Background: to assess the efficiency and effectiveness of the organizational system of a Clinical Pharmacological Service of an Italian tertiary care teaching hospital in providing advices (CPAs) to clinicians within timeframes useful for the personalization of antimicrobial dosing regimens in different patients’ populations according to the clinical benefit for patient care. Methods: the frequency per week of the various typologies of CPA were defined on the basis of prior evaluations aimed at estimating the clinical benefit for patient care (high priority level, for antimicrobials used to treat acute infections in the critically ill patients; moderate priority level, for those used to treat cytomegalovirus infections in solid organ transplant recipients; mild priority level, for those used to treat chronic infections). The CPAs provided between December 2011and June 2012 represented the starting database. The measured turnaround time (TAT) of each CPA typology was used as an indicator of the performance of the organizational system according to a predefined scale (high, when within agreed timeframe; acceptable, when 1-2 days overdue; low, when > 2 days overdue). Results: 6601 CPAs were provided (77.4% for AOUD and 22.6% for other hospitals), mainly for antimicrobials with high priority. The mean TAT was of < 24 hours for the CPAs provided 3 to 5 times per week, of < 48 hours for those provided 2 times per week, and of < 6 days for those provided once weekly or every over week. Overall, the performance was high, the percentage of overdue advices always less than 5%, irrespective of the CPA type. Conclusions: our study confirms the suitability of the organizational system of our Service to provide a thousand per month TDM-based CPAs within timeframes clinically useful for the individualization of the dosing regimens of several antimicrobials.